2013
DOI: 10.1016/j.resuscitation.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest due to drowning among children and adults from the Utstein Osaka Project

Abstract: Background Children have better outcomes after out-of-hospital cardiac arrest (OHCA) than adults. However, little is known about the difference in outcomes between children and adults after OHCA due to drowning. Objectives The aim of this study is to assess the outcome after OHCA due to drowning between children and adults. Our hypothesis is that outcomes after OHCA due to drowning would be in better among children (<18 years old) compared with adults (≥18 years old). Method This prospective population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…A previous study indicated that the proportion of survivors with favorable neurologic outcomes after OHCAs, which were caused by drowning irrespective of location and behavior, was 0.8%. 34 Another study also reported that the proportion of survivors with favorable neurologic outcomes after bystanderwitnessed OHCA of cardiac origin was 5.4% at home and 20.8% in public places. 35 The outcomes of our study subjects were much poorer compared with these results.…”
Section: Figurementioning
confidence: 96%
“…A previous study indicated that the proportion of survivors with favorable neurologic outcomes after OHCAs, which were caused by drowning irrespective of location and behavior, was 0.8%. 34 Another study also reported that the proportion of survivors with favorable neurologic outcomes after bystanderwitnessed OHCA of cardiac origin was 5.4% at home and 20.8% in public places. 35 The outcomes of our study subjects were much poorer compared with these results.…”
Section: Figurementioning
confidence: 96%
“…For the critical outcome of favorable neurologic outcome, we found very-low-quality evidence (downgraded for indirectness and imprecision) from 1 observational study 62 involving 1737 patients. Univariate analysis reported by the study authors indicates an unadjusted OR for good outcomes in the group where submersion was witnessed (OR, 16.33; 95% CI, 5.58-47.77).…”
Section: Witnessed Statusmentioning
confidence: 99%
“…For the critical outcome of survival, we found lowquality evidence (downgraded for risk of bias, indirectness, and imprecision) from 4 studies 62,68,69,71 involving a total of 2857 victims. Two studies 67,69 were from the same EMS system, and both used multivariate analysis.…”
Section: Witnessed Statusmentioning
confidence: 99%
See 2 more Smart Citations